2014
DOI: 10.1080/19942060.2014.11083308
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Flow Fields In Single Board Computer Cabin Systems Using CFD Analysis

Abstract: A detailed computational fluid dynamics (CFD) analysis of the cooling of a single board computer (SBC) cabin system is performed using the CFD software FLO EFD 9.0. Air-cooling and water-cooling are used for all major heat generating components with the attached heat sinks in it. North bridge chip, SODIMM memory module and south bridge chip are cooled by airflow. A liquid-cooling system with the microchannel heat sink is used to enhance heat transfer from the CPU. The simulation results show that all the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The rst application of the combined CFD-DEM model was reported to be the solid particle plug ow in a horizontal tube [16], and then many others have been devoted to the analysis and simulation of various aspects of uidized beds using coupled CFD-DEM calculations [17]. In the coupled solution process, the ow eld is treated as a continuous phase and the solid phase is treated as a discrete phase, and the corresponding solutions for the ow eld and the particle phase are obtained by the coupled calculation of the two software [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The rst application of the combined CFD-DEM model was reported to be the solid particle plug ow in a horizontal tube [16], and then many others have been devoted to the analysis and simulation of various aspects of uidized beds using coupled CFD-DEM calculations [17]. In the coupled solution process, the ow eld is treated as a continuous phase and the solid phase is treated as a discrete phase, and the corresponding solutions for the ow eld and the particle phase are obtained by the coupled calculation of the two software [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The insertion of turbulators and vortex generators (Ts-VGs) inside channel heat exchangers (CHEs) is well-known for its efficiency to enhance the convective heat transfer [1][2][3][4][5][6][7]. Several studies have been reported on CHEs equipped with various types of obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative results showed that the trapezoidal-shape porous-type inserts increase the heat transfer by about 13.8% in the case of 1.7 kPa of pressure penalty and 6.4 kg/s of fluid mass. Using the FLO EFD 9.0 type CFD software, Xu et al (2014) conducted a detailed numerical analysis of the flow fields as well as the isotherms in a computer board. The whole system adopted the combination of liquidtype cooling and air-type cooling to increase heat transfer.…”
Section: Introductionmentioning
confidence: 99%